Lipopolysaccharide‐induced maternal inflammation induces direct placental injury without alteration in placental blood flow and induces a secondary fetal intestinal injury that persists into adulthood. (25th January 2018) - Fricke, Erin M.; Elgin, Timothy G.; Gong, Huiyu; Reese, Jeff; Gibson‐Corley, Katherine N.; Weiss, Robert M.; Zimmerman, Kathy; Bowdler, Noelle C.; Kalantera, Karen M.; Mills, David A.; Underwood, Mark A.; McElroy, Steven J.
Abstract : Problem: Premature birth complicates 10%‐12% of deliveries. Infection and inflammation are the most common etiologies and are associated with increased offspring morbidity and mortality. We hypothesize that lipopolysaccharide (LPS)‐induced maternal inflammation causes direct placenta injury and subsequent injury to the fetal intestine. Method of study: Pregnant C57Bl6 mice were injected intraperitoneally on day 15.5 with 100 μg/kg LPS or saline. Maternal serum, amniotic fluid, placental samples, and ileal samples of offspring were obtained assessed for inflammation and/or injury. Maternal placental ultrasounds were performed. Placental DNA was isolated for microbiome analysis. Results: Maternal injection with LPS caused elevated IL‐1β, IL‐10, IL‐6, KC‐GRO, and TNF. Placental tissue showed increased IL‐1β, IL‐6, and KC‐GRO and decreased IL‐10, but no changes were observed in amniotic fluid. Placental histology demonstrated LPS‐induced increases in mineralization and necrosis, but no difference in placental blood flow. Most placentas had no detectable microbiome. Exposure to maternal LPS induced significant injury to the ilea of the offspring. Conclusion: Lipopolysaccharide causes a maternal inflammatory response that is mirrored in the placenta. Placental histology demonstrates structural changes; however, placental blood flow is preserved. LPS also induces an indirect intestinal injury in the offspring that lasts beyond the neonatal period.